Exploring The Intersection Of AI And Business Ethics: A Qualitative Study On Digital Marketing Development In Indonesia - Ekawahyu Kasih; Ngadi Permana; Farah Qalbia; Muhamad Chaidir (Proceeding of The International Conference on Business and Economics, 2023)
This research delves into the nuanced landscape of digital marketing evolution in Indonesia, particularly at the intersection of artificial intelligence (AI) and business ethics. The study aims to elucidate the current state of digital marketing practices in Indonesia, exploring how AI technologies are integrated and the ethical considerations surrounding their implementation. Employing a qualitative research approach, the study utilizes in-depth interviews and focus group discussions with key stakeholders in the Indonesian digital marketing ecosystem. The sampling technique involves purposive sampling to ensure representation from various industry sectors and perspectives. Data analysis is conducted through thematic analysis, allowing for the identification of emerging themes and patterns related to AI adoption and ethical implications in digital marketing strategies. Preliminary findings suggest a complex interplay between technological advancements, ethical dilemmas, and regulatory frameworks, highlighting the need for a balanced approach to AI utilization in digital marketing within the Indonesian context.